2018
DOI: 10.1158/1078-0432.ccr-18-0421
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of a Guadecitabine (SGI-110) and Irinotecan in Metastatic Colorectal Cancer Patients Previously Exposed to Irinotecan

Abstract: Chemotherapeutic resistance eventually develops in all patients with metastatic colorectal cancer (mCRC). Gene silencing through promoter demethylation is one potential reversible mechanism of resistance with administration of hypomethylating agents. We evaluated the safety and tolerability of guadecitabine and irinotecan in patients with mCRC previously treated with irinotecan. In this 3+3 dose-escalation study, patients with mCRC previously exposed to irinotecan received guadecitabine days 1 to 5 of a 28-day… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…Of note, exposure to decitabine generated from guadecitabine, as assessed by AUC inf , was lower in our study than that observed in ovarian cancer (38) and hepatocellular carcinoma (36), but was comparable with exposure previously reported for myeloid malignancies (35) and colorectal cancer (37).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Of note, exposure to decitabine generated from guadecitabine, as assessed by AUC inf , was lower in our study than that observed in ovarian cancer (38) and hepatocellular carcinoma (36), but was comparable with exposure previously reported for myeloid malignancies (35) and colorectal cancer (37).…”
Section: Discussionsupporting
confidence: 87%
“…No AEs other than those typically reported with guadecitabine (35) or ipilimumab (11) monotherapy were observed, including no unexpected or potentially additive toxicities, thus supporting the feasibility of the explored therapeutic sequence at all doses of guadecitabine investigated. In contrast, severe myelosuppression was reported in several other studies of guadecitabine in solid tumors (36)(37)(38), leading to lower MTDs of 30-45 mg/m 2 /day. In the ovary and colorectal studies (37,38), coadministration of guadecitabine with myelosuppressive chemotherapy undoubtedly affected overall tolerability, suggesting additive toxicity, unlike our results using the combination of guadecitabine and checkpoint blockade.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Patients with metastatic colorectal cancer eventually develop imbalances in promotor methylation, which can result e.g., in reduced expression of tumor suppressor genes and in resistance to chemotherapy. Hypomethylating agents can reverse this resistance mechanism by promotor demethylation and subsequent gene expression reactivation (Lee et al, 2018). In fact, tumor suppressor genes were found re-expressed by DNA methyltransferase enzyme inhibitors (DNMTi) in colorectal cancer cell lines (Bosch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Hypomethylating agents (HMAs) were approved for treatment of hematologic malignancies, but with little success in solid tumors (Azad et al, 2017;Lee et al, 2018). EGFR promoter hypermethylation in colorectal cancer has been found associated with patient resistance to anti-EGFR therapies (Jueliger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%